PENGARUH GAYA BELAJAR VISUAL, LINGKUNGAN BELAJAR DAN MINAT BELAJAR TERHADAP PRESTASI BELAJAR MATA PELAJARAN IPS TERPADU - Fadila Maya Safira; Ninik Indawati; Waluyo Edi (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2017)
Visual learning style is a learning style which is done by observing or comprehending something by using the sense of sight in the form of images, illustrations or graphs. In addition to the visual learning style, students' learning environment should be conducive so that students are easier to comprehend the materials taught. Learning environment is a place of teaching and learning activities which includes students’ external and internal responses. Besides, the higher students’ interest encourages students' learning achievement. Learning interest is a sense of students’ attraction or tendency towards an activity to acquire information or experiences that suit students’ needs. This study is aimed of finding out the effect of visual learning style, learning environment and learning interest on the students’ learning achievement of Integrated Social Science lesson. This study employed quantitative research, ex-post facto research. The total number of samples used in this study were 85 students by using proportional random sampling technique. Data collection techniques used were questionnaires and documentation. Data analysis techniques used were classical assumption test, descriptive analysis, multiple linear regression analysis and hypothesis test. The result of the analysis shows that 21,4% is influenced simultaneously.